2021
DOI: 10.3390/md19060333
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Illudalane Sesquiterpenes from the Marine Sediment Ascomycete Aspergillus oryzae

Abstract: The new asperorlactone (1), along with the known illudalane sesquiterpene echinolactone D (2), two known pyrones, 4-(hydroxymethyl)-5-hydroxy-2H-pyran-2-one (3) and its acetate 4, and 4-hydroxybenzaldehyde (5), were isolated from a culture of Aspergillus oryzae, collected from Red Sea marine sediments. The structure of asperorlactone (1) was elucidated by HR-ESIMS, 1D, and 2D NMR, and a comparison between experimental and DFT calculated electronic circular dichroism (ECD) spectra. This is the first report of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The experimental procedures used in this study were reported previously [ 38 , 39 ]. The 1 H, 13 C NMR and 2D NMR spectra were recorded on a Bruker AMX-700 spectrometer with tetramethylsilane (TMS) as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental procedures used in this study were reported previously [ 38 , 39 ]. The 1 H, 13 C NMR and 2D NMR spectra were recorded on a Bruker AMX-700 spectrometer with tetramethylsilane (TMS) as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…The fungal strain was recognized as Penicillium chrysogenum (GenBank accession No. MH127462), according to DNA amplification sequencing of the fungal ITS region, as reported before [ 38 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…144 Other Aspergillus strains were the source of viomellein derivatives 308 and 309, 145 polyketides 310 and 311 (the latter a known synthetic derivative but new NP), 146 156 and sesquiterpenoid lactone 335. 157 Aspergillus oryzae, isolated from a Red Sea sediment, yielded asporychalasin 336, a cytochalasin with a 6/6/11 skeleton. 158 Aspergillus strains derived from so corals were the source of cyclic hexapeptides 337-339, 159 lipodepsipeptide 340, 159 2pyrone derivatives 341 and 342, cyclopentenone derivative 343 and austocystin derivative 344.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…Orfali et al [ 27 ] first discovered two illudalane sesquiterpenes, asperorlactone ( 41 ) and echinolactone D ( 42 ), from marine sediment ascomycete Aspergillus oryzae , in which compound 41 has an absolute configuration of (5R). Compounds 41 and 42 showed antiproliferative activity against human lung cancer (A549), liver cancer (HepG2), and breast cancer (MCF-7) cell lines, with half maximal inhibitory concentration (IC 50 ) values of asperorlactone ( 41 ) <100 µM.…”
Section: Bioactivity Of Sesquiterpenoids From Aspergillus ...mentioning
confidence: 99%
“…According to this report, Orfali et al speculated a biosynthetic pathway of asperorlactone ( 41 ), in which illudol was a key intermediate. The iluane-type sesquiterpene asperorlactone can be synthesized by dehydration, oxidation, and four-membered ring opening [ 27 ].…”
Section: Chemical Synthesis and Biosynthesis Of Sesquiterpenoids From...mentioning
confidence: 99%